2012
DOI: 10.1016/j.actatropica.2011.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Malaria in India: The Center for the Study of Complex Malaria in India

Abstract: Malaria is a major public health problem in India and one which contributes significantly to the overall malaria burden in Southeast Asia. The National Vector Borne Disease Control Program of India reported ~1.6 million cases and ~1100 malaria deaths in 2009. Some experts argue that this is a serious underestimation and that the actual number of malaria cases per year is likely between 9 and 50 times greater, with an approximate 13-fold underestimation of malaria-related mortality. The difficulty in making the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
120
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(122 citation statements)
references
References 34 publications
2
120
0
Order By: Relevance
“…3 Recently, it has been suggested that VBDs incidence is between 9 and 50 times greater than reported with approximately 13 fold under estimation of malaria-related mortality. 4 The failure to cap the resurgence of VBDs and the continuing increased incidence of them is warranting a more proactive approach for their prevention.…”
Section: Introductionmentioning
confidence: 99%
“…3 Recently, it has been suggested that VBDs incidence is between 9 and 50 times greater than reported with approximately 13 fold under estimation of malaria-related mortality. 4 The failure to cap the resurgence of VBDs and the continuing increased incidence of them is warranting a more proactive approach for their prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Acidosis, cerebral involvement, renal impairment, and chronic illness were key independent predictors for a poor outcome in African children with severe malaria (von Seidlein et al 2012). The current case data is included in our recent case series publication on P. vivax-associated AKI (Kute et al 2012) The multidisciplinary approach that integrates clinical and field studies with laboratory, molecular, and genomic methods will provide a powerful combination for malaria control and prevention in India (Srivastava and Yadav 2000;Yadav et al 1998;Das et al 2012). …”
Section: Discussionmentioning
confidence: 97%
“…This facilitates the parasite to escape the host protective immunity, furthermore the development of drug resistance. Efforts are in progress to develop newer genetic sequencing technologies to identify early treatment failure with chloroquine in vivax malaria 10. As per the 2012 WHO recommendation artesunate combination therapy are recommended especially in areas of documented chloroquine resistance for rapid and effective clearance of P. vivax along with a 14-day course of primaquine 11…”
Section: Discussionmentioning
confidence: 99%